2018
DOI: 10.1007/s13364-018-0392-y
|View full text |Cite
|
Sign up to set email alerts
|

Body temperature variation in free-living and food-deprived yellow-necked mice sustains an adaptive framework for endothermic thermoregulation

Abstract: In many mammalian species, variation in body temperature (T b) exceeds the values suitable for defining homeothermy, making it justifiable and even necessary to resort to the term Bheterothermic^. However, T b data are only available for ca. 1% of extant mammalian species. We investigated variations in T b in wild free-living and experimentally food-deprived yellow-necked mice Apodemus flavicollis, during the temperate-zone autumn-winter period. In line with the adaptive framework for endothermic thermoregulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Apodemus mice possess several traits that enable them to evade diurnal activity. They dominate over competitors such as bank voles [60], consume and store high-energy food [31], and can slow down their metabolism under certain circumstances [61,62]. In addition, sharpened sensory capabilities make them well-equipped to survive nocturnal predation attempts [23].…”
Section: Discussionmentioning
confidence: 99%
“…Apodemus mice possess several traits that enable them to evade diurnal activity. They dominate over competitors such as bank voles [60], consume and store high-energy food [31], and can slow down their metabolism under certain circumstances [61,62]. In addition, sharpened sensory capabilities make them well-equipped to survive nocturnal predation attempts [23].…”
Section: Discussionmentioning
confidence: 99%
“…To measure the metabolic rate and T b over a ∼24 h period (for details, see section “DEE during fasting”), we used another 30 mice (15 individuals from each year) captured in 20 traps set randomly during both years in mid-winter in the vicinity of the fixed 0.9 ha research plot (at a distance of ∼100–300 m). After ∼1 week of acclimation to laboratory conditions, those animals were intraperitoneally surgically implanted with miniaturized, paraffin wax-coated T b data loggers (procedure as described in Boratyński et al (2018 , 2019 )). The loggers (logger size = 14 mm × 14 mm, mass = 1.8 g, resolution = 0.0625°C) were set to record T b every 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…In turn, during the autumn of the 2nd year, mice were maintained under laboratory conditions for ∼1 week following measurement. Once RMR had been recorded (within 1–2 days after capture), 6 of the mice in autumn of the 2nd year were implanted intraperitoneally with miniaturised paraffin wax-coated T b data-loggers, prior to release at the place of capture (for details, see Boratyński et al 2018 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of a variety of species indicated that hibernation (multi‐day torpor) and daily torpor (lasting <24 h) lower the energy expenditure associated with BMR by ~95% and ~65%, respectively (Ruf & Geiser, 2015 ). Several factors can trigger heterothermy use (Geiser & Brigham, 2012 ) but, the general function of torpor is to balance the energy budget, and individuals flexibly use this strategy in response to current energetic requirements (Boratyński et al., 2018 ; Boyles et al., 2007 ; Bozinovic et al., 2007 ; Eto et al., 2015 ; Fjelldal et al., 2021 ; Vuarin et al., 2013 ; Wojciechowski et al., 2007 ). Moreover, studies have found consistent among‐individual variation in torpor use, and less or more heterothermic animals co‐occur within populations (Boratyński et al., 2019 ; Dammhahn et al., 2017 ; Nespolo et al., 2010 ; Tapper et al., 2021 ), suggesting the existence of a continuum in thermoregulatory strategies (Angilletta et al., 2010 ; Boratyński et al., 2019 ; Boyles et al., 2013 ).…”
Section: Introductionmentioning
confidence: 99%